2004
DOI: 10.1093/nar/gkh304
|View full text |Cite
|
Sign up to set email alerts
|

Integration of the 5' end of the retrotransposon, R2Bm, can be complemented by homologous recombination

Abstract: R2Bm is a non-long-terminal-repeat (non-LTR) retrotransposon that was identified at a specific target site in the 28S rRNA genes of the silkworm, Bombyx mori. Although in vitro analysis has revealed that the 3' end of R2Bm is integrated into the target site by means of target-primed reverse transcription (TPRT), the mechanism of the 5' end integration is not well understood. We established a novel in vivo system to assay the insertion mechanism of R2Bm using a cultured cell line, C65, and a baculovirus, AcNPV,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
1

Year Published

2005
2005
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 27 publications
0
22
1
Order By: Relevance
“…This may be due to the replacement of upstream 28S sequences and R1-5′UTR to polyhedrin 5′UTR and GST sequence. The inclusion of 28S sequence to its 5′ termini of the construct achieved intact 5′ junction formation in R2 (26,29), so it may be the same for R1. This implicates that the free ends generated during this process are repaired by the cellular proteins.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…This may be due to the replacement of upstream 28S sequences and R1-5′UTR to polyhedrin 5′UTR and GST sequence. The inclusion of 28S sequence to its 5′ termini of the construct achieved intact 5′ junction formation in R2 (26,29), so it may be the same for R1. This implicates that the free ends generated during this process are repaired by the cellular proteins.…”
Section: Discussionmentioning
confidence: 96%
“…The newly cloned R1 from the silkworm genome was found to be active for retrotransposition, and it turned out that the baculovirus-based in vivo retrotransposition assay could be applied to the study of various site-specific LINEs (17,26). The most distinctive feature of R1 retrotransposition is its requirement of 3′ downstream sequence derived from 28S gene for the precise, efficient integration into its target DNA.…”
Section: Discussionmentioning
confidence: 99%
“…Transposable elements (TEs) were the most represented group of sequences in the SSH with 37 clones displaying significant similarity to Pol-like proteins of non-long terminal repeat (non-LTR) retrotransposons, such as R2Bm from the silk moth, Bombyx mori [57], MsquI-Aa2 from the mosquito, Aedes aegypti [58], and bilbo from the fruit fly, Drosophila subobscura [59] among others (Table 3). TEs are genetic entities capable of insertion at different positions in the genome and of inducing alteration of the function of the genes with which they become associated [60].…”
Section: Transposable Elementsmentioning
confidence: 99%
“…5D, 4 and 5). Homologous recombinational repair is thought to facilitate R2 5Ј-end integration (Fujimoto et al 2004) and was reported for L1s integrating into pre-existing older L1 elements, resulting in hybrid or toggled insertions Symer et al 2002). Unlike this special case of toggled insertions, where host DNA had prior homology to the retrotransposon allowing for detectable sequence changes after recombination, a more general case will involve recombination between identical stretches of DNA, and no sequence changes will be produced.…”
Section: Model Of 5ј-end Attachment and L1 Integrationmentioning
confidence: 99%